Implementation of the Flag Raising Troops Program Policy at the Pancasila Ideology Development Agency - Gilang Hardiono; Ermaya Suradinata; Ahmad Averus (INFOKUM, 2025)
This study discusses the implementation of the Paskibraka Program policy by BPIP as a strategic effort in forming a young generation with Pancasila character. The main problem in this study is how this policy is implemented by BPIP and what factors support and hinder the implementation of the policy throughout Indonesia. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, documentation studies, and observations. Informants were selected using purposive sampling and snowball sampling techniques, involving BPIP officials, the Provincial Kesbangpol, and DPPI. The instruments used were interview guidelines, recording devices, and policy documents as analysis materials. The results of the study indicate that the implementation of the policy generally runs according to the direction of the regulation, with several challenges such as limited resources in the regions, less than optimal cross-agency communication, and differences in understanding the redefinition of the Paskibraka program. Supporting factors include regulatory support, BPIP's commitment as the main sponsor, and the existence of supporting organizations such as DPPI. This study concludes that the success of policy implementation is highly dependent on synergy between stakeholders, clarity of institutional roles, and optimization of existing resources. The recommendations submitted include the preparation of a national master plan, strengthening the coordinating role of BPIP, and expanding partnership networks in the regions as a strategic step in fostering the Pancasila ideology in a sustainable manner.